Potential integration of small ruminants with tree-cropping systems in Asia and the South Pacific - Devendra, C.
(Fr, Es)
Ilus., 28 ref.
Keywords: AGROFORESTERIA; RUMIANTE; FERTILIDAD DEL SUELO; ESCARDA; MALEZAS; ITALIA; REVISTA MUNDIAL DE ZOOTECNIA